AKSI PEPELINGAN (PENYULUHAN PEDULI LINGKUNGAN) - Aprilia Mukaromatun Barokah; Santia Ningrum; Bayu Adi Laksono (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Mangkubumi especially Sambongpari is still not aware of the environment. In addition, the source of water for rice fields is still using flowing rivers. This can make the river contaminated from household waste and garbage which is feared to affect the quality of crops and have an impact on human health. MCK is not in accordance with applicable regulations and well spacing is also not appropriate will cause soil contamination and soil pollution occurs. this is exacerbated by a consumptive society and a lack of community action in caring for the environment. in this case the researcher observes the activities carried out by the community regarding the area that will be used as the object of counseling. identification of problems and potential environmental impacts of observed activities. identify patterns of change or problems that arise. this asks questions to community leaders and related parties concerned with environmental care counseling related to the behavior and habits of the Mangkubumi community in order to find out how far the community has knowledge about environmental issues and how far they care about the environment. this will provide solutions and solutions to existing problems from environmental awareness counseling actions. This program was carried out on October 28, 2022 with the theme "My Actions for My Earth" PPPHL and the local community. The presentation of the material was carried out very well, while the form of tree planting and mutual cooperation was carried out on October, 30 2022 for one full day. Tree seeds for tree planting were obtained from the forestry service, this tree planting event was highly appreciated by the forestry service because planting trees is like giving good life to other living things. Developing environmental education programs in schools and educational institutions to increase public awareness, starting from the child level to maturity. Support plastic waste reduction initiatives by providing eco-friendly alternatives and educational campaigns. Involving the community in critical land rehabilitation programs and restoring natural ecosystem functions. Providing information and tips to the public on how to save energy and water to the community.